ANALISIS DAMPAK PANDEMI COVID-19 TERHADAP KINERJA KEUANGAN DAERAH - Keri Saroh Isti'anah; Ari Nurul Fatimah (Transpublika Publisher, 2023)
The COVID-19 pandemic is an outbreak of an infectious disease originating from the SARS-Cov-2 virus. As the virus grows, it causes various problems in various areas of life in society. The impact felt was so real with the cases of high death rates, unstable economy and other problems. The government, which has an obligation to make people's welfare take various policies to overcome this problem. From policy making, surely, it intersects with state finances which will ultimately affect the financial performance of the government itself. The purpose of this research is to determine the impact of the COVID-19 pandemic on the financial performance of local governments. The method used in writing this article is a qualitative method in the form of a literature review. The data obtained comes from secondary data, namely in the form of indirect retrieval via Google Scholar, Sinta and several articles that support the concept of the theme ranging from 2017-2022. The results of this study show that there have been changes in Indonesia's economic quarter and the regional budget experienced a minus number. Even so, the influence of the Covid-19 pandemic did not have a significant impact on the financial performance of local governments in several regions in Indonesia.